The Evolution of Woman. George Eliot’s“Woman in France: Madame de Sablé” - Barbara Pauk (Cahiers Victoriens et Edouardiens)
George Eliot’s engagement with gender ideology has often been discussed in relation to her novels even though she expresses her views on the so-called “woman question”much earlier, in her journalistic work. She was a contributor to the radical Westminster Review and, from 1852–54, also its editor. The various readings of one of her essays “Woman in France: Madame de Sablé”, published anonymously in 1854, reflect the very different ways in which Eliot’s position regarding the woman question has been interpreted. For Shirley Foster, who compares her to the notorious antifeminist Sarah Ellis, the essay documents her antifeminism. Other critics, who mention this rarely-analysed essay, use it to illustrate Eliot’s feminist credo or, like Frederick R. Karl, find the text a contradictory one. The central claim of this essay is that in “Woman in France” Eliot makes a clearly feminist statement, expressed in a very subtle and innovative way. My argument will demonstrate that the variety of readings is due to the fact that the references to French women and French writers have often been overlooked.